Formação de ligações carbono-nitrogênio e carbonocalcogênio catalisadas por iodeto de cobre: síntese de 2- (organocalcogenil)-indolizinas - Goulart, Tales Antonio Camargo (2018)
The copper-catalyzed cyclization of propargylpyridines with diorganyl dichalcogenides was applied to the synthesis of 2-(organochalcogenyl)-indolizines. A systematic study of the cyclization system revealed that the mutual action between copper(I) iodide and diorganyl dichalcogenides is essential for the formation of 2- (organochalcogenyl)-indolizines in good yields avoiding the formation of hydrogenated indolizine. The standard reactional conditions with the use of propargylpyridines (0.25 mmol), diorganyl dichalcogenides (0.375 mmol), copper (I) Iodide (20 mol%), sodium carbonate (0.50 mmol) in DMF (3 mL) were compatible with many replacements in the substrate, such as methyl, chlorine, fluoride, methoxyl and trifluoromethyl. This protocol was efficient with diorganyl diselenides and ditellurides but ineffective with diorganyl disulfides. Through this methodology, 27 new molecules were obtained with yields ranging from 21 to 84%. In addition, the 2- (organochalcogenyl)-Indolizines obtained were easily transformed into more complex products using reactions in cross-coupling conditions of the Suzuki type catalyzed by palladium salts with bronic acids. Condition which provided 3 new examples of the 2- aryl-indolizinas with yields of 38 to 73%.